Assessing Students’ Problem-Solving Ability on Renewable Energy Topics in Physics: A Rasch Analysis Based on Heller’s Framework - Welli Andriani; Irma Rahma Suwarma; Ida Kaniawati (Jurnal Pendidikan Progresif, 2026)
This study examined students’ problem-solving ability in physics on renewable energy topics by evaluating a Heller-based assessment instrument using the Rasch model. The study focused on determining whether the instrument functioned adequately for profiling students’ staged problem-solving performance and identifying how item difficulty was distributed across the Heller framework. A quantitative descriptive design was employed involving 35 students who completed five renewable-energy physics problems. The instrument consisted of 25 scored indicators representing five Heller stages: Focus the Problem, Describe the Physics, Plan the Solution, Execute the Plan, and Evaluate the Answer. Students’ written responses were assessed using a 0–4 polytomous rubric. The data were analyzed using MINISTEP VERSION 5.11.2 to examine person and item reliability, separation indices, item fit, person fit, unidimensionality, item difficulty, and rating-scale functioning. The instrument demonstrated adequate psychometric quality for exploratory use. Person reliability was 0.89, item reliability was 0.86, person separation was 2.83, and item separation was 2.49. All 25 indicators met acceptable Rasch fit criteria, while 32 of 35 students showed response patterns consistent with model expectations. The unidimensionality analysis supported the presence of a dominant primary dimension, and the 0–4 rating categories functioned progressively. The item difficulty distribution showed that students’ performance was influenced not only by the formal Heller stage but also by the conceptual and contextual demands of each renewable-energy problem. The Heller-based instrument was suitable for preliminary profiling of students’ problem-solving ability in renewable-energy physics. However, further validation with larger and more diverse samples is recommended to strengthen the instrument’s reliability, fairness, and instructional usefulness. Keywords: renewable energy, physics problem solving, rasch analysis, heller’s framework, cational assessment.